Mapping nutrient resorption efficiencies of subarctic cryptogams and seed plants onto the Tree of Life. Issue 11 (7th May 2014) - Lang, Simone I.; Aerts, Rien; van Logtestijn, Richard S. P.; Schweikert, Wenka; Klahn, Thorsten; Quested, Helen M.; van Hal, Jurgen R.; Cornelissen, Johannes H. C.
Abstract Nutrient resorption from senescing photosynthetic organs is a powerful mechanism for conserving nitrogen (N) and phosphorus (P) in infertile environments. Evolution has resulted in enhanced differentiation of conducting tissues to facilitate transport of photosynthate to other plant parts, ultimately leading to phloem. Such tissues may also serve to translocate N and P to other plant parts upon their senescence. Therefore, we hypothesize that nutrient resorption efficiency (RE, % of nutrient pool exported) should correspond with the degree of specialization of these conducting tissues across the autotrophic branches of the Tree of Life. To test this hypothesis, we had to compare members of different plant clades and lichens within a climatic region, to minimize confounding effects of climatic drivers on nutrient resorption. Thus, we compared RE among wide‐ranging basal clades from the principally N‐limited subarctic region, employing a novel method to correct for mass loss during senescence. Even with the limited numbers of species available for certain clades in this region, we found some consistent patterns. Mosses, lichens, and lycophytes generally showed low REN (<20%), liverworts and conifers intermediate (40%) and monilophytes, eudicots, and monocots high (>70%). REP appeared higher in eudicots and liverworts than in mosses. Within mosses, taxa with more efficient conductance also showed higher REN. The differences in REN among clades broadly matched the degree of specialization of conducting tissues. This novel mapping of a physiological process onto the Tree of Life broadly supports the idea that the evolution of conducting tissues toward specialized phloem has aided land plants to optimize their internal nitrogen recycling. The generality of evolutionary lines in conducting tissues and nutrient resorption efficiency needs to be tested across different floras in different climatic regions with different levels of N versus P availability.